Estimation of the Rate of Soil Erosion in the Tasik Chini Catchment, Malaysia using the RUSLE Model Integrated with the GIS - Islam, Mir Sujaul; Muhammad Barzani, Gasim; B. S., Ismail; A. R., Sahibin; T., Mohd Ekhwan (AENSI Publishing, 2012)
The Tasik Chini Catchment, located at the southeast region of Pahang, Malaysia is experiencing soil erosion problems which are of environmental concern. So a study was conducted that involved the integration of the Revised Universal Soil Loss Equation (RUSLE) with the Geographic Information System (GIS) to estimate potential soil loss and identify erosion risk areas. Values for the model on rainfall erosivity (R), topographic factors (LS), land cover (C) and management factors (P) were calculated from rainfall data, together with the use of topographic and land use maps. Soil was analyzed for obtaining the soil erodibility factor (K). Physical properties such as particle size distribution, texture, hydraulic conductivity and organic matter content (OM) were analyzed to support the erosion rate analysis. The mean soil erodibility factors varied from 0.03 to 0.30 Mg h MJ-1 mm-1. From a total of eleven soil series studied, soil erosion results showed that the five soil series with low rate of soil loss were: Tebok, Lating, Bungor, Kekura and Gong Chenak. Two soil series with moderate soil loss were Serdang and Prang. Two soil series with moderately high rate of soil loss were Kuala Brang and Rasau. The Malacca soil series had high erosion rate. The worst-case scenario was the Kedah soil series. The soil erosion potential zones were classified into five classes namely very low, low, moderately high, high and very high soil loss. The results indicated that 71.54% of the study area lay within the very low erosion risk class, 2.94% in the low erosion risk class, 3.38% in the moderately high erosion risk class, 1.45% in the high erosion risk class and 13.25% in the very high erosion risk class. This high erosion rate is expected to generate high sediment yield influx into the water bodies of Tasik Chini making the lake shallower and perhaps even non existent in the near future if precautionary measures are not taken.